Locally Freezing Control via Superhydrophobic Patterns on Hydrophilic Substrates - Dong Song; Jiacheng Zhang; Changsheng Xu; Xiang Wang; Sihan Huang; Pengcheng Ye (Journal of Marine Science and Engineering)
Ice accumulation on cold surfaces presents significant operational and safety challenges in various fields such as power transmission, aviation, and polar marine transportation. This study investigates the effectiveness of selectively applied superhydrophobic patterns on hydrophilic substrates to locally control freezing behaviors. The freezing dynamics of water droplets impacting surfaces with hybrid wettability patterns were investigated experimentally under cold conditions. The results demonstrate that superhydrophobic surfaces significantly reduce the freezing rate due to decreased contact time and the contact region. By selectively placing superhydrophobic patterns on hydrophilic surfaces, the location of ice formation could be effectively manipulated. The use of multiple superhydrophobic stripes was found to segment the impacting droplets into several parts, implying the ability to selectively avoid ice accumulation at specific areas. Furthermore, experiments identified critical temperature thresholds at which the effectiveness of superhydrophobic stripes diminishes. When the temperature of the substrate is higher than −25 °C, the superhydrophobic stripes can sufficiently divide an impacting droplet leaving no ice at the superhydrophobic region. In the tested temperature range between −25 °C and −40 °C, the ice coverage ratio at the superhydrophobic region increases as temperature decreases, with a maximum value of 25.6 ± 2.33% at −40 °C. Superhydrophobic patterns also exhibited improved deicing efficiency during melting processes, highlighting their potential for robust ice management applications.